Cannabinoids attenuate the effects of aging upon neuroinflammation and neurogenesis - Yannick Marchalant; Holly M. Brothers; Greg J. Norman; Kate Karelina; A. Courtney DeVries; Gary L. Wenk (Neurobiology of Disease, 2009)
WIN-55,212-2 (WIN-2) can elicit anti-inflammatory and cognitive-enhancing effect in aged rats. The current study was designed to determine the differential role of the endocannabinoid receptor sub-types 1 (CB1) and 2 (CB2) and transient receptor potential vanilloid 1 receptor (TRPV1) in the reduction of age-associated brain inflammation and their effects on neurogenesis in the dentate gyrus of aged rats. Our results demonstrate that 1) the antagonist actions of WIN-2 at the TRPV1 receptor are responsible for the reduction in microglial activation and 2) the agonist actions of WIN-2 at CB1/2 receptors can trigger neurogenesis in the hippocampus of aged rats. Chronic treatment with WIN-2 established an anti-inflammatory cytokine profile within the hippocampus. Our results provide insight into the role of the endocannabinoid and vanilloid systems upon two different and detrimental aspects of normal and pathological aging, chronic neuroinflammation and decline in neurogenesis.